NOUNS’ SIGNS OF HELONG LANGUAGE - Dominikus Tauk; Maria Osmunda Eawea Monny; Kaminton Tambunan (Postgraduate School, Universitas Nusa Cendana, 2022)
This article shows and analyses forms, meaning and functions of nouns’ signs of Helong language. The method used in this research is field method with taking note technique and recording. The results of this research shows that there are three nouns’ signs of Helong language that are categorized into: basic forms, combine forms and gemination forms (due to phonological process). There are three basic noun forms of some relative distances, those are -a (that/close to the speaker); -ia (this/close to the speaker) and –ua (far from the speaker). There are three forms of positions’ signs due to the combination of preposition -ne and nouns, those are: nia (ne + -a), nua (ne + ia, = ni) and nua (ne + -ua). There are fifteen forms of nouns gemination due to phonological process are: nga, ngua, ngia, sia, sia, sua, tia, ta, tua, pa, pia, pua dan ra, ria, rua.